Analysis Of Rice Milling Feasibility Mansyaul Huda Trading Business In Trimomukti Village, Candipuro District, South Lampung Regency - Ariyanti, Ariyanti; Istanto, Istanto; Wibowo, Hendri; Dewi Hastuti (Jurnal Ekonomi, 2024)
Rice farming is one of the businesses in the agricultural sector that is applied by people in various regions to meet their daily needs. Post-harvest processing technology is certainly needed to increase farmers' income through rice milling which has a great influence on determining the quality of crop yields. Rice milling is a meeting place between production, post-harvest, processing, marketing, and rice so that it is an important link in supplying national rice which is required to be able to contribute to the provision of rice, both in terms of quantity and quality. This study aims to find out the total cost, total revenue, total income and feasibility analysis of  rice milling business. Mansyaul Huda in Trimomukti Village, Candipuro District, South Lampung Regency. The method used in this study is using quantitative analysis, which is one type of research that aims to analyze factually and accurately, while the implementation method carried out in this study is the case study method. The results of the study show that the total cost incurred by rice milling is Rp.6,624,056,325, total revenue is Rp.7,545,260,000, total income is Rp.921,203,675 and business feasibility analysis with a result of 1.13. The results of the study mean that the  rice milling business. Mansyaul Huda is very profitable and worthy of effort or it can also be interpreted that every rice milling business spends or sacrifices a cost of Rp. 1,- then gets a revenue of Rp.1.13 in the rice milling business. Mansyaul Huda.